PSEUDOEXHAUSTIVE RAM TESTING - V. N. Yarmolik; I. Mrozek; B. A. Levantsevich (Informatika)
Modern RAM tests and methods for their generation are analyzed and investigated. The wide application of pseudoexhaustive tests as the main test procedure for modern computer systems has been proved. The main estimates and metrics for so kind of tests are obtained. The values of analytical estimates have been validated by the experimental investigations.